Resusitasi Cairan pada Pasien dengan Syok Hipovolemik - Meylia Nabilla Putri; Anna Millizia (STIKES Columbia Asia Medan, 2025)
Hypovolemic shock is a condition of reduced organ perfusion and oxygenation to tissues caused by acute loss of blood (hemorrhagic shock) or body fluids (non-hemorrhagic) which can be caused by various circumstances resulting in multiorgan failure. The mortality rate in injured patients who experience hypovolemic shock in clinics with a total care level reaches 6%. Relevant articles were searched through an electronic database, Google Scholar, using the keywords “Fluid Resuscitation in Patients with Hypovolemic Shock”. The treatment to prevent hypovolemic shock is fluid resuscitation. The classic symptoms of shock are, blood pressure decreases dramatically and is not stable even though the position is lying down, the patient suffers from severe tachycardia, oliguria, agitation or confusion, increased sympathetic work, hyperventilation, collapsed veins, release of stress hormones and large expansion to fill the volume of blood vessels using interstitial fluid, intercellular fluid and reduce urine production. Management of hypovolemic shock due to fixed bleeding begins with an assessment of airway, breathing, circulation, diability and exposure. Then after initial management, the response is evaluated, which can be rapid, temporary, and minimal or no response.